Efeito tipo-antidepressivo do derivado piperazínico 2,6-di-terc-butil-4-((4-(2-hidroxietil)piperazina-1-il)metil)fenol (LQFM212) e possíveis mecanismos de ação envolvidos - Moreira, Lorrane Kelle da Silva (2023)
Depressive disorders affect individuals worldwide and may also be associated with other mental disorders such as anxiety disorders. Despite advances to improve understanding of the neurobiology of depressive disorders, no single established mechanism per se can explain all facets of these disorders and the available drugs often show therapeutic delay for clinical effectiveness. A plethora of results show the effects of piperazine derivatives on the central nervous system and are indicators of its therapeutic potential for treating mental disorders. Previously, it was shown that the piperazine derivative 2,6-di-tert-butyl-4-((4-(2-hydroxyethyl)piperazin-1-yl)methyl)phenol (LQFM212) has anxiolytic-like activity which involves serotonergic pathway, nicotinic receptors and BZD-site of GABAA receptor, without cognitive impairments. In this regard, since the same compound can have anxiolytic as well as antidepressant effects, the aim of this research was to evaluate the possible antidepressant-like activity of the compound LQFM212. Swiss albino male mice orally treated with LQFM212 (54 μmol/kg) showed behavioral effects related to antidepressant-like activity, in the forced swimming test (FST), after treatment with a single dose or with repeated doses for 15 consecutive days. Pretreatment with WAY-100635 (0.7 μmol/kg), p-chlorophenylalanine (500 μmol/kg), prazosin (2.6 μmol/kg), SCH-23390 (15 μg/kg), sulpiride (146 μmol/kg) ou α-methyl-p-tyrosine (512 μmol/kg) reversed the antidepressant-like effect of LQFM212 in the FST. Furthermore, repeated treatment with LQFM212 increased hippocampal brain-derived neurotrophic factor (BDNF) levels. Regarding the monitoring of body weight and the evaluation of possible biochemical changes the treatment with repeated doses with LQFM212 (54 μmol/kg) did not change: animals' body weight, liver glutathione (GSH) levels, and serum levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), urea and creatinine. A possible action of the compound LQFM212 on inflammatory parameters, in mice, was evaluated by systemic inflammation by the lipopolysaccharide (LPS)-induced neuroinflammation model and by local inflammation by the carrageenan- or LPS-induced pleurisy model. In the LPS-induced neuroinflammation model, oral treatment with LQFM212 (54 μmol/kg) reversed the anxiety-like and depression-like behaviors, in the open field, forced swimming and tail suspension tests, the increase of pro-inflammatory cytokines (TNF-α and IL-1β) and the decrease of anti-inflammatory cytokines (IL-4 and IL-10), into animals’ serum, caused by intraperitoneal administration of LPS (1 mg/kg). In this same model, treatment with LQFM212 (54 μmol/kg) also attenuated oxidative stress-related changes, demonstrated by reduced nitrite levels and myeloperoxidase (MPO) activity, and increased glutathione levels in the prefrontal cortex and hippocampus, and also reduced cholinesterase activity in the whole brain, of animals that received intraperitoneal administration of LPS (1 mg/kg). On the other hand, oral treatment with LQFM212 (54 μmol/kg) failed to reduce the increase in cell migration and pro-inflammatory cytokines (TNF-α and IL-1β) in pleural exudate caused by intrapleural administration of 1% carrageenan or LPS (250 ng/mL) in the pleurisy model. In addition to the reduction in MPO activity seen in the LPS-induced neuroinflammation model, treatment with LQFM212 (54 μmol/kg) also reduced the activity of this enzyme in the pleural exudate of animals subjected to the carrageenan- or LPS-induced pleurisy model. Taken together, the results showed that treatment with LQFM212 promotes behavioral changes suggestive of antidepressant-like activity in mice, which probably involve the monoaminergic pathways, in addition to increased hippocampal levels of BDNF, suggesting changes in synaptic neuroplasticity possibly as a mechanism underlying the antidepressant-like effect of the compound. The effects found in the LPS-induced neuroinflammation model did not seem to be secondary to a peripheral anti-inflammatory action of LQFM212, since this compound failed to reduce the changes caused by carrageenan or LPS in the pleurisy model. On the other hand, treatment with LQFM212 reduced MPO enzyme activity in pleural exudate, prefrontal cortex, and hippocampus, and increased per se GSH levels in both brain regions mentioned above, thus suggesting a possible antioxidant activity in vivo that may contribute to the effects observed in the neuroinflammation and pleurisy model.